Business Paradigm through Brand Experience as A Business Concept (Case Study on J.CO Suzuya Mall Rantauprapat) - Lahmuddin Lahmuddin; Ade Parlaungan Nasution; Nurintan Asyiah Siregar (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
Many franchise businesses at this time became one of the pillars of economic growth in Indonesia. One of these franchise businesses is J.CO. The company owned by Jhonny Andrean was founded in 2003, and has spread throughout Indonesia and even to various countries. J.CO Donuts and Cafe occupies the fourth position in fast food brands in 2021, making J.CO one of the fast-food brands that is quite well known among Indonesians, especially in Labuhanbatu Regency. The purpose of this study is to determine the effect of user experience and brand experience at J. CO Donuts outlets on repurchase intention. CO Donuts outlets on repurchase interest experienced by consumers in Labuhanbatu Regency, and through this study want to know the marketing concept applied by J.CO so that it becomes a well-known fast food company in Indonesia, especially in Labuhanbatu Regency. This type of research is an associative type of research with the approach used is a quantitative approach. The population used in this study were consumers and customers of J.CO at Suzuya Mall Rantauprapat with a purposive random sampling sample. The results showed that user experience had an insignificant effect on repurchase interest, and brand experience had a positive and significant effect on repurchase interest in J.CO products at Suzuya Mall Rantauprapat.